2020
DOI: 10.1519/jsc.0000000000003674
|View full text |Cite
|
Sign up to set email alerts
|

Different Foot Positioning During Calf Training to Induce Portion-Specific Gastrocnemius Muscle Hypertrophy

Abstract: Nunes, JP, Costa, BDV, Kassiano, W, Kunevaliki, G, Castro-e-Souza, P, Rodacki, ALF, Fortes, LS, and Cyrino, ES. Different foot positioning during calf training to induce portion-specific gastrocnemius muscle hypertrophy. J Strength Cond Res 34(8): 2347–2351, 2020—The aim of this study was to compare the changes in gastrocnemius muscle thickness (MT) between conditions such as which foot was pointed outward (FPO), foot was pointed inward (FPI), or foot was pointed forward (FPF). Twenty-two young men (23 ± 4 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…In support, the authors show excellent reliability for cross-sectional area, muscle thickness, and echo intensity determined from panoramic and a single transverse image for the biceps brachii with strong a strong association between muscle cross-sectional area and muscle thickness (r = 0.93). The interrater image acquisition reliability values for muscle thickness obtained in the transverse and sagittal planes show good–excellent reliability with minimal difference values sensitive enough to detect resistance training-induced increases in muscle thickness following longer (>6 weeks) training interventions [ 5 , 27 , 28 ], but likely not short-term training induced hypertrophy [ 29 ]. The SEM for muscle thickness measurements during acquisition are similar to those shown by a single experienced sonographer [ 30 ] and those by Mayer et al [ 11 ] with raters of different experience level.…”
Section: Discussionmentioning
confidence: 99%
“…In support, the authors show excellent reliability for cross-sectional area, muscle thickness, and echo intensity determined from panoramic and a single transverse image for the biceps brachii with strong a strong association between muscle cross-sectional area and muscle thickness (r = 0.93). The interrater image acquisition reliability values for muscle thickness obtained in the transverse and sagittal planes show good–excellent reliability with minimal difference values sensitive enough to detect resistance training-induced increases in muscle thickness following longer (>6 weeks) training interventions [ 5 , 27 , 28 ], but likely not short-term training induced hypertrophy [ 29 ]. The SEM for muscle thickness measurements during acquisition are similar to those shown by a single experienced sonographer [ 30 ] and those by Mayer et al [ 11 ] with raters of different experience level.…”
Section: Discussionmentioning
confidence: 99%
“…B-mode ultrasonography (LOGIQ e V2; GE Healthcare Japan, Tokyo, Japan) with an 8 MHz linear array probe was used to evaluate the muscle thickness and the pennation angle of the medial and lateral gastrocnemius muscles (MG and LG, respectively). Longitudinal ultrasound images were obtained for the MG and LG at 30% of the lower-leg length, measured from the popliteal crease to the lateral malleolus near the point of the maximal cross-sectional area of the lower leg (Akagi and Takahashi, 2013;Nakamura et al, 2014;Nunes et al, 2020a). Additionally, a longitudinal ultrasound image of the soleus muscle was obtained at 50% of the lower-leg length (Kubo et al, 2014(Kubo et al, , 2017.…”
Section: Muscle Thickness Pennation Angle and Fascicle Lengthmentioning
confidence: 99%
“…The effectiveness of resistance training (RT) programs depends on appropriate control of training volume and intensity [1][2][3]. Therefore, the proper manipulation of choice of resistance, exercise selection, and order, number of sets and repetitions, the velocity of muscle action, rest period length, and frequency can limit training plateaus and improve the ability to increase muscle mass [e. g., muscle thickness (MT)] [4][5][6]. Some investigations have shown that muscle growth seems to occur non-uniformly in the longitudinal axis of the muscles [7][8][9].…”
Section: Introductionmentioning
confidence: 99%